Access to school-based eye health programs in Central Region, Malawi: a qualitative case study. (8th March 2023) - Yashadhana, Aryati; Lee, Ling; Serova, Nina; Nthete, Evaristous; Burnett, Anthea M
Summary: Vision impairment among children is associated with lower levels of educational attainment. School-based eye health programs have the potential to provide high-quality and cost-effective services that assist in the prevention of blindness and uncorrected vision impairment, particularly in low-resources settings. The aim of this study was to identify key factors that inhibit or facilitate the provision of school-based eye health programs, including referral to eye care services, for Malawian children in the Central Region. In-depth interviews ( n = 10) and focus groups ( n = 5) with children, parents, school staff, eye care practitioners, government and NGO workers (total participants n = 44) in rural and urban contexts within central region, Malawi, were conducted. Taking a rights-based approach, we used the AAAQ (availability, accessibility, acceptability, quality) framework to identify barriers and enablers to school eye health programs. Complex factors shape access to school-based eye health programs. While intersectoral collaboration between ministries was present, infrastructure and resourcing restricted the delivery of school eye health programs. School staff were supportive of being trained as vision screeners. Parents voiced geographic access to follow up eye care, and spectacle cost as a barrier; and children revealed experiences of stigma related to spectacle as barriers to uptake. School-based eye care may be facilitated through teachers, community informants and health workers through; the provision of school vision screening; increased awareness of the impact of vision impairment on education and future employment; and through educational approaches that seek to decrease stigma and misconceptions associated with wearing spectacles.